PENINGKATAN WISATAWAN MASA NEW NORMAL: STRATEGI KOMUNIKASI PEMASARAN DI DINAS PARIWISATA KOTA DENPASAR - Suryaningsih, Ida Ayu Anggreni; Gayatri Kesumayathi, Ida Ayu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Since the issuance of regulations related to the implementation of the new normal phase in all regions of Indonesia, the Government of Denpasar city, assisted by the Covid-19 Response Acceleration Task Force, has begun to start designing new normal SOPs for all related aspects one of which is in terms of increasing tourists. The new normal policy made by the central government needs a marketing strategy adapted to the situations and conditions that occurred during the pandemic. This study aimed to determine the marketing communication strategy of the Denpasar City Tourism Office in increasing tourists during the new normal period. This study uses the theory of marketing mix. The research method used in this study is a qualitative descriptive method, in which the Denpasar City Tourism Office was taken as the object of research. Data collection was carried out using observation, documentation, and interview techniques. The data then were analyzed in three stages, namely data reduction, data presentation, and conclusions. The results of the study reported that the Denpasar City Tourism Office has taken steps that are in accordance with the marketing communication strategy, the steps are the implementation of marketing mix with promotion mix inside.